Pengaruh Squat Training Terhadap Peningkatan Daya Ledak Otot - Erna Sariana; Mohammad Ali; Muhammad Naufal Fazqa (Jurnal Fisioterapi dan Kesehatan Indonesia, 2021)
Introduction: Explosive power is a combination of strength and speed of dynamic and explosive muscle contraction that involves the expenditure of maximum muscle strength in a short time, by having good explosive power, a person will be easier to master the basic techniques of a sport. One way that can be done to increase explosive power is to dovariations squat, which is an exercise. Movement weight training, i.e. exercise using external weights. Objective: This study aims to determine the effect ofvariations squat on muscle explosive power from various literatures. Method: Using a literature study design, with published literature a maximum span of the past 10 years. Literature is obtained from three search engines, namely: PubMed, Science Direct and the Garuda Portal. Results: A total of 170 literatures were obtained with nine literatures relevant to this literature study. The results show that the variation intraining is squat effective in increasing muscle explosive power. Conclusion: Overall, this study saw an increase in muscle power by providing variations intraining squat. However, the results of this study are not accurate enough due to differences in movement, duration, intensity, and sport branches.